2015
DOI: 10.1371/journal.pone.0138527
|View full text |Cite
|
Sign up to set email alerts
|

Genetically and Phenotypically Distinct Pseudomonas aeruginosa Cystic Fibrosis Isolates Share a Core Proteomic Signature

Abstract: The opportunistic pathogen Pseudomonas aeruginosa is among the main colonizers of the lungs of cystic fibrosis (CF) patients. We have isolated and sequenced several P. aeruginosa isolates from the sputum of CF patients and compared them with each other and with the model strain PAO1. Phenotypic analysis of CF isolates showed significant variability in colonization and virulence-related traits suggesting different strategies for adaptation to the CF lung. Genomic analysis indicated these strains shared a large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
49
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 67 publications
7
49
0
Order By: Relevance
“…As such, the aim of our study was to address this current gap of knowledge with respect to the adaptation of P. aeruginosa in nCFB. Indeed, we found similar adaptation strategies between isolates of P. aeruginosa from nCFB patientswhich, due to the broad range of environmental niches, display a wide spectrum of virulence and motility (Pujana et al, 1999;Penesyan et al, 2015). While differences in airway characteristics exist between CF and nCFB, we have found that P. aeruginosa largely adapts in a similar manner, extending from virulence factor production to motility and biofilm formation, and that virulence tends to decrease over time.…”
Section: Expression Of Virulence Factors By P Aeruginosa Generally Dsupporting
confidence: 63%
“…As such, the aim of our study was to address this current gap of knowledge with respect to the adaptation of P. aeruginosa in nCFB. Indeed, we found similar adaptation strategies between isolates of P. aeruginosa from nCFB patientswhich, due to the broad range of environmental niches, display a wide spectrum of virulence and motility (Pujana et al, 1999;Penesyan et al, 2015). While differences in airway characteristics exist between CF and nCFB, we have found that P. aeruginosa largely adapts in a similar manner, extending from virulence factor production to motility and biofilm formation, and that virulence tends to decrease over time.…”
Section: Expression Of Virulence Factors By P Aeruginosa Generally Dsupporting
confidence: 63%
“…Bacteriostatic Assay-The clinically relevant Pseudomonas aeruginosa PASS1 strain was isolated and cultured to mid-log growth phase as previously described (60,61). PASS1 was then washed twice in 1ϫ PBS and diluted to an OD 600 nm of 0.1 in Luria Beria broth before use.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported whole genome sequences and global proteomic characterisation from four CF isolate strains of P. aeruginosa grown in LB medium 11 . This showed that CF strains had similar sized genomes (ranging 6.1-6.4Mbp) and shared common core features, many of which were different to PAO1.…”
mentioning
confidence: 99%